Development of a More Effective Mosquito Trapping Box for Vector Control - Tanawat Chaiphongpachara; Ploypailin Bunyuen; Kitthisak Khlaeo Chansukh (The Scientific World Journal)
Mosquito-borne diseases are a major public health issue in nearly all tropical and subtropical countries, making vector control imperative. The mosquito trapping box is one type of mosquito traps that is popular in some areas because it is affordable, environmentally friendly, and easy to produce. This research investigated whether the effectiveness of the mosquito trapping box could be increased through the addition of various physical factors, including a wooden frame, black cotton cloth, a fan, carbon dioxide (CO2), and heat, by testing a range of box designs in the Samut Songkhram Province, Thailand, between December 2016 and January 2017. We found that trapping boxes constructed with Pinus kesiya wood caught more mosquitoes than those constructed with two other types of wood or aluminum. We also found that mosquito trapping boxes were more effective when more factors were added, although these differences were only significant for black cotton cloth and CO2. These findings will guide the future development of mosquito trapping boxes for effective mosquito control in other areas, helping to reduce the incidence of mosquito-borne diseases.